Clinical Expression of Leber Hereditary Optic Neuropathy Is Affected by the Mitochondrial DNA–Haplogroup Background - Hudson, Gavin; Carelli, Valerio; Spruijt, Liesbeth; Gerards, Mike; Mowbray, Catherine; Achilli, Alessandro; Pyle, Angela; Elson, Joanna; Howell, Neil; La Morgia, Chiara; Valentino, Maria Lucia; Huoponen, Kirsi; et al. (American journal of human genetics, 2007)
Leber hereditary optic neuropathy (LHON) is due primarily to one of three common point mutations of mitochondrial DNA (mtDNA), but the incomplete penetrance implicates additional genetic or environmental factors in the pathophysiology of the disorder. Both the 11778G→A and 14484T→C LHON mutations are preferentially found on a specific mtDNA genetic background, but 3460G→A is not. However, there is no clear evidence that any background influences clinical penetrance in any of these mutations. By studying 3,613 subjects from 159 LHON-affected pedigrees, we show that the risk of visual failure is greater when the 11778G→A or 14484T→C mutations are present in specific subgroups of haplogroup J (J2 for 11778G→A and J1 for 14484T→C) and when the 3460G→A mutation is present in haplogroup K. By contrast, the risk of visual failure is significantly less when 11778G→A occurs in haplogroup H. Substitutions on MTCYB provide an explanation for these findings, which demonstrate that common genetic variants have a marked effect on the expression of an ostensibly monogenic mtDNA disorder.